Analisis Produktivitas Alat Excavator Pada Pekerjaan Galian Proyek Revitalisasi Danau Bakuok Kabupaten Kampar - Dame Simamora; Bochari; Safridatul 'Audah; Joleha; Imam Suprayogi; Randhi Saily (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2025)
Excavation activities require the support of heavy equipment to ensure effective and efficient field operations. The utilization of appropriate heavy machinery plays a crucial role in accelerating project execution and achieving predetermined construction targets. This research aims to analyze the productivity levels of various types of excavators and to estimate the duration of excavation work. The study employs both primary data, obtained through direct field observations, and secondary data, collected from interviews with relevant authorities. The research was conducted as part of the Lake Bakuok Revitalization Project (Phase III) in Aursati Village, Tambang District, Kampar Regency, Riau Province. The results indicate that the standard arm excavator achieved a productivity rate of 189.629 m³/hour, the long arm excavator recorded 97.332 m³/hour, while the amphibious excavator demonstrated a productivity of 48.150 m³/hour.